Stres Keluarga Pasien Di ICU Salah Satu Rumah Sakit Swasta di Yogyakakarta - Margaretha Kurniastuti (Jurnal Indonesia Sehat, 2024)
Background: Stress because of stressors. One source of stress for the patient's family is when one of the members is treated in the ICU. Various changes when a family member is being treated can trigger prolonged stress. Lack of patient information during treatment is one of the causes of stress in the family. Objective: To determine the description of stress in patient families in the Intensive Care Unit of a Private Hospital in Yogyakarta. Methodology: This type of research is quantitative descriptive with cross-sectional approach and total of 51 respondents using consecutive sampling techniques. The research instrument used Perceived Stress Scale 10 (PSS-10). Univariate analysis to find out and describe description of each variable consisting of age, gender, and stress. The research location was carried out in the Intensive Care Unit (ICU) room at a private hospital in Yogyakarta City. Results: The results of the study showed that the characteristics of the respondents were 37 people or 72.5% female, the ages of the respondents were mostly in the 46 -55 years age group, totaling 24 people or 47.1%. Description of the stress level of the families of Intensive Care Unit patients: 39 people or 76.5% of respondents were in a state of moderate stress and 10 people or 19.6% were in a state of severe stress. Conclusion: The stress level of the families of Intensive Care Unit patients in one of the private hospitals in Yogyakarta is mostly moderate to severe stress. So the importance of information from medical staff in helping reduce the stress level of families of critical patients in the ICU.